Islam and Buddhism: similarities of moral practices - Mohd Nor, Nur Suriya (2019)
Islamic moral system is not only defining morality, but also guides the human on how to achieve it, at both an individual as well as collective level. It stems from its primary creed of belief in One God as the Creator and Sustainer of the Universe. Islam considers the human being to be a part of God’s creation, and as His subjects. The purpose of human life in Islam is to worship Allah by leading this worldly life in harmony with Divine Will. According to Venerable K.Sri Dhammananda, Buddhist morality is concerned with our relationship with ourselves and with other beings. The requirement for morality arises from the fact that nobody is perfect by nature, thus human beings have to train themselves to be good. Thus, morality becomes the most essential aspect of living. The practice of morality or good conduct in Buddhism includes the practice of right speech, right action, and right livelihood. This study shall focus on similarities of moral practices between Islam and Buddhism with a view of encouraging Buddhists to learn about the Islamic tradition and also to explain certain central concepts of Buddhism to Muslims who are unfamiliar with the Buddhist tradition as a way to increase their knowledge towards a better understanding of other religions. The similarities found between Islam and Buddhism would conduce acknowledgement and respect of one another on both sides. This is in keeping with the Qu’rÉnic vision of mutual recognition and mutual respect i.e. tÉ’ruf between the Muslims and other worlds communities and traditions.